Site-specific dual functionalization of cysteine residue in peptides and proteins with 2-azidoacrylates - Ariyasu, Shinya (2022)
Herein, we report use of 2-azidoacrylates to perform site-specific dual functionalization of the cysteine residue of peptides and bovine serum albumin (BSA), a native protein containing one free cysteine residue. The sulfhydryl group of the cysteine residue could be conjugated with 2-azidoacrylates bearing various functionalities, such as fluorescent dyes under physiological aqueous buffer conditions, to afford peptide and protein conjugates anchoring an azide moiety. Successive azide-alkyne cycloaddition enables installation of the second functionality, thus affording dual-functionalized peptide- and protein-based materials.